The Methodology of Working the Landscape Composition of the Kohitang Mountain in the Glossy of Colors (Journal of Universal Science Research, 2023)
This article explores the methodology behind creating a visually captivating landscape composition of the Kohitang Mountain, highlighting the brilliant interplay of colors that enrich its scenic beauty. From understanding the unique topography of the mountain to employing various techniques and artistic choices, this article provides insights into the process of capturing the essence of Kohitang Mountain's natural splendor through vibrant colors. Whether you are an artist seeking inspiration or a nature enthusiast eager to understand the artistic interpretation of landscapes, this article offers valuable information on creating visually stunning compositions. The Kohitang Mountain stands as a majestic natural wonder, captivating the beholder with its awe-inspiring beauty.